the Optical Properties of Electrostatic Design and Study Mirror By using Bimurzaev Technique - Mohammed, Intehaa A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research a computational simulation  has been carried out on the design and properties of the electrostatic mirror and a mathematical expression has been suggested  to represent the axial potential of an electrostatic mirror. The electron beam path using the Bimurzaev  technique had been investigated as mirror trajectory with the aid of Runge â€“ Kutta  method. The spherical and chromatic aberration coefficients of mirror has computed and normalized in terms of the focal length. The choice of the mirror depends on the operational requirements. The Electrode shape of mirror two electrodes has been determined by using package SIMION computer program. Computations have shown that the suggested potentials give good result for low value spherical and chromatic aberration Cs/Fr= - 8.05, Cc/Fr=- 9.1, L=8mm, A=500volt, which give a good  indicator for designing the mirrors